Bargaining, vertical mergers and entry - Geza Sapi (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
This paper analyzes vertical integration incentives in a bilaterally duopolistic industry where upstream producers bargain with downstream retailers on terms of supply. In the applied framework integration does not affect the total output produced, but it affects the distribution of rents among players. Vertical integration incentives depend on the strength of substitutability or complementarity between products and the shape of the unit cost function. I demonstrate furthermore that in contrast to the widely prevailing view in competition policy, vertical integration can under particular circumstances convey more bargaining power to the merged entity than a horizontal merger to monopoly. The model is applied to analyze strategic merger incentives to influence entry decisions. Mergers can facilitate and deter entry. While horizontal mergers to deter entry are never profitable, firms on different market levels may strategically choose to integrate vertically to keep a potential entrant out of the market. I provide conditions for such entry-deterring vertical mergers to occur.
Keywords: L13; L22; L42; 330; Bargaining; Vertical Mergers; Entry